Usucapião quarentenária sobre terras do estado: fundamentos jurídicos, atualidade e repercussão na questão agrária brasileira - Grande Júnior, Cláudio (2012)
This dissertation analyzes the old quarantiner prescription on state lands, if indeed that legal institution was valid in Brazil, how and when it ceased to be accepted by the legal system, because even today it is eventually sought the recognition of such prescription, consummated before the outset of the legality of the Civil Code of 1916, and how all that affects the agrarian issue. This dissertation aims to scrutinize the original legal foundations of that old original prescription of forty years, on state assets, especially on vacant lands, without losing sight of some of its possible consequences for the agrarian issue. The hypothetical-deductive method is used for research and understanding of legal rules, alongside the historical investigation of events, processes, institutions and judgeship of the past, followed by the dialectical method to overcome points of divergence found in the bibliography search. Thus it is demonstrated how, in the late nineteenth and early twentieth century, a legal discourse on prescriptibility of certain state assets was built, including the vacant lands. It can also explains how the legal discourse was dismantled to build the current one, which preconizes the imprescriptibility of all public property, including of the vacant lands. The results make evident how exactly the understanding set out in Summula 340 of STF was built, and its limitations, which says little about the prescription of state assets before the Civil Code of 1916. Another result is the demonstration of the impossibility of state property being usucapted in Brazil before the Land Law of 1850, which made clear that only after that the conditions for both were signed, albeit with additional difficulties for vacant lands.